The Effect of Drama-Based Social Studies Education on Psychological Resilience and Well-Being Levels of Secondary School Students Affected by the Earthquake - Bayram, Hüseyin (Alberta Journal of Educational Research, 2024)
The aim of this research is to examine the effect of drama-based social studies education on the psychological resilience and well-being levels of secondary school students affected by the earthquake that took place in Turkey in 2023. The embedded design from mixed methodology was used in the research. The participant group of the research was formed by multi-stage mixed sampling method. A total of 57 middle school fifth grade students, 28 in the experimental group and 29 in the control group, took part in the experimental research. The data of the research were collected with Stirling Children's Well-being Scale, Child and Youth Resilience Measure-12, semi-structured interview forms, and unstructured observations. Independent samples t-test, analysis of covariance, and content analysis were used to analyse the data of the research in which quantitative and qualitative data were collected together. Research findings concluded that drama-based social studies education increased students' psychological resilience and well-being levels. It was also determined that the students perceived that drama-based social studies education contributed to their resilience, self-belief, calmness, happiness, playfulness, and helped them to deal with challenges, reduce stress, and eliminate anxiety. The results suggest that researchers and educational planners would be well served to increase the use of drama in social studies courses to improve students' psychological resilience and well-being levels.